The path to Kina convertibility: An analysis of Papua New Guinea's foreign exchange market - Martin Davies; Marcel Schröder (Asian Development Bank (ADB), 2022)
Papua New Guinea (PNG) has faced a foreign exchange (forex) shortage since 2015. To protect reserves, the Bank of PNG has resorted to forex rationing that led to a large backlog of orders and import compression. This paper surveys the structure of PNG's forex market and analyzes recent market conditions. We argue that the various policy proposals being discussed currently in PNG are inadequate to restore currency convertibility. For this, a real exchange rate depreciation is required instead. We develop a forex market model that features a backlog of unmet orders, which suggests that a frontloaded depreciation is preferred to an often-favored gradual adjustment. Empirical results indicate that the government's large budget deficits have contributed to the forex shortage, which highlight the need for greater fiscal restraint. In the longer term, we argue for more exchange rate flexibility and forex allocation through competitive auction.
Keywords: F31; O23; Q32; 330; foreign exchange shortage; foreign exchange rationing; currency convertibility; Papua New Guinea